Severe Acute Inflammatory Demyelinating Polyradiculoneuropathy With Persistent Weakness Associated With Tumor-Like Nerve Root Enlargement. Issue 4 (June 2015) - Stoll, Sharon S.; Rakocevic, Goran
Abstract : Abstract: We report a 23-year-old woman with rapid onset of proximal and distal limb weakness and areflexia, associated with tumor-like spinal nerve root enlargement and markedly elevated cerebrospinal fluid protein. Our patient developed the inability to walk within days, without preceding illness. Within two weeks, she had near-complete bilateral wrist and foot drop. Her cranial nerves and respiratory function remained intact. She received intravenous immunoglobulin early on for suspected Guillain-barre syndrome but remained wheelchair-bound until 6 Plasma exchange sessions were completed. After that, she continued to improve with intravenous immunoglobulin dosed every 3–4 weeks. Prominent demyelinating features were found on NCS, with cerebrospinal fluid protein of 415 mg/dL. Comprehensive infectious work-up was negative. Magnetic resonance imaging of lumbosacral and cervical spine showed tumor-like masses mistaken for neurofibromatosis (axial diameter, 7.5–10 mm). Repeated magnetic resonance imaging 6 months later showed persistent nerve root enlargement, despite the patient's improved functional status.